PERSPEKTIF KEADILAN: PERTANGGUNGJAWABAN HUKUM ATAS TERJADINYA NURSING ERROR TERHADAP PASIEN RUMAH SAKIT DI INDONESIA - Retias Dewi Jayanti (Universitas Muhammadiyah Metro, 2022)
Law Number 36 of 2009 concerning Health Article 4 states that everyone has the right to health. Therefore every individual, family and community has the right to obtain protection for their health, and the state is responsible for regulating the fulfillment of the right to a healthy life for its population. In the context of meeting the basic human needs for health, health efforts are organized in the form of individual health efforts and public health efforts. The number of cases occur such as errors in the assessment of problems faced by patients, errors in planning nursing actions, errors in the provision of nursing actions, errors in documenting and errors in administering drugs. Errors in drug administration can be fatal and very detrimental to patients both physically and materially. The problem to be discussed in this research is the form of legal liability for the occurrence of Nursing Error in the perspective of justice towards patients. The method used in this research is Normative Jurisdiction analysis through literature review and related documents. Based on the results of research that in the form of accountability Nurses' responsibility will depend on the form of authority possessed. In the case of violation of the authority of attribution which is the independent function of the nurse, if there is an error in the nursing care, the nurse will assume the burden of his own responsibility. Legal protection for nurses is still minimal. The relationship between doctors and nurses in providing health care to patients is a more binding partnership where there should be harmonization of duties, roles and responsibilities and an open system. Legal responsibility in health services performed by health workers, there are 3 (three) legal forms, namely civil, criminal and administrative law.